2018
DOI: 10.1016/j.jcma.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Association between allergic diseases, allergic sensitization and attention-deficit/hyperactivity disorder in children: A large-scale, population-based study

Abstract: Our results suggest that AD and asthma with allergic sensitization are associated with ADHD in children. As allergic sensitization is an increased factor of developing allergic diseases, early control of environmental and allergens exposure could help to modify the burden of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
3
36
0
1
Order By: Relevance
“…ADHD is associated with allergic diseases such as asthma, allergic rhinitis and atopic dermatitis. The immune response to these allergic diseases are known to increase the risk of neurodevelopmental diseases by affecting the central nervous system (37,38). In a study about allergic disease and inflammation in ADHD, allergic diseases, Ig-E and eosinophil levels were higher in the ADHD group (39).…”
Section: Discussionmentioning
confidence: 99%
“…ADHD is associated with allergic diseases such as asthma, allergic rhinitis and atopic dermatitis. The immune response to these allergic diseases are known to increase the risk of neurodevelopmental diseases by affecting the central nervous system (37,38). In a study about allergic disease and inflammation in ADHD, allergic diseases, Ig-E and eosinophil levels were higher in the ADHD group (39).…”
Section: Discussionmentioning
confidence: 99%
“…We generated regression models with additional adjustment for maternal smoking during pregnancy, 29 maternal alcohol consumption during pregnancy, 30 breastfeeding, 31 preterm birth, 32 birth weight, 33 and number of siblings 34 to assess those associations with ADHD symptoms. Finally, we excluded children with allergic diseases (defined as having physician-diagnosed eczema, allergic conjunctivitis, and/or asthma), 35 congenital heart diseases, 36 preterm birth, 32 or low birth weight (defined as birth weight <2500 g) 33 as a group potentially with greater baseline risk for ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no association of this IL-1RN polymorphism with ADHD was found in a larger sample [41]. Comorbidity with allergic and autoimmune disorders such as atopic eczema, allergic rhinitis and asthma is another factor that could increase the risk for ADHD and future research may lead to a better understanding of the mechanisms underlying the observed comorbidity [38,[42][43][44]. In a meta-analysis and a large-scale genome-wide association study (GWAS), associations between asthma and ADHD were found in both children and adults [45,46].…”
Section: Inflammation and The Relationship With Adhdmentioning
confidence: 95%